Physicochemical and Microstructural Properties of Yoghurt Fortified with Anthocyanin Black Glutinous Rice (Oryza sativa L. var. glutinosa) Extract - Pambudi, Ridho; Nurdin, Muhammad Alfan; Lailasari, Umi; Shodiq, Berliana Arifa Noer; Prasetiyo, Dimas Teguh (Faculty of Animal Science Universitas Brawijaya, 2024)
Anthocyanin has great potential as a natural additive to improve the quality of yoghurt drink and give more benefits for health. This research aimed to analyze the effect of adding anthocyanin black glutinous rice extract on the physicochemical and microstructural quality of yoghurt drink. The research material is skim milk, yoghurt starter, and anthocyanin extract of black glutinous rice. The method used in this study was a laboratory experiment with a Completely Randomized Design (CRD) with four treatments and three replications. The treatment given was the addition of anthocyanin extract from black glutinous rice with concentrations of 0% (P0), 10% (P1), 20% (P2), and 30% (P3). The variables observed were the total acid, pH, syneresis, viscosity, water holding capacity, particle size, and distribution. Data were analyzed by analysis of variance (ANOVA), and if there was a difference, the analysis was continued using Tukey's Test. The results showed that the addition of the anthocyanin extract of black glutinous rice had a significant effect (p < 0.05) on the total acid, viscosity, water holding capacity, particle size, and particle distribution and no significant effect (p > 0.05) on the pH and syneresis. The addition of anthocyanin extract black glutinous rice increases total acid, viscosity water holding capacity and reduces pH, syneresis, particle size, and distribution. This study concludes that the addition of anthocyanin extract of black glutinous rice until 30% has a good effect on improving the physicochemical and microstructural quality of yoghurt drink.